The Bacillus subtilis spo0B stage 0 sporulation operon encodes an essential GTP-binding protein. - Trach, K (1989)
Transcription of the spo0B gene and genes downstream of it was investigated by S1 nuclease protection experiments. The spo0B gene was transcribed from a single promoter, and this transcript extended through a gene, obg, coding for a 47,668 Mr protein. Transcription of this operon ended in a stem-loop structure. The sequence of the deduced obg protein contained a region with homology to known GTP-binding proteins in the nucleotide-binding regions. The amino-terminal portion of this protein showed homology to mammalian collagen, suggesting a structural role. The purified obg protein was shown to bind [alpha-32P]GTP in vitro. Several attempts to inactivate the obg gene were unsuccessful, indicating that the obg gene product was essential for growth. The possible function of this protein and its relationship to RAS-like proteins and sporulation was discussed. Immediately downstream of the obg gene were two genes involved in phenylalanine biosynthesis, pheB and pheA. The pheA gene coded for monofunctional prephenate dehydratase, on the basis of the high homology of the deduced amino acid sequence to prephenate dehydratases of bacterial origin. The sequence of the pheB gene product was not homologous to chorismate mutase, and its function remains unknown. Transcription of the phe genes was shown to begin at the stem-loop structure between obg and pheB. The possibility was entertained that phe gene transcription arises from processing or antitermination of the spo0B transcript.